Voices unheard, insights into the lives of people with disabilities: A needs assessment study - Samaneh Sargazi; Nikoo Yamani; Arash Najimi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The phenomenon of disability in society is as ancient as human history itself. Approximately one billion people worldwide experience some form of disability, with a fifth of these individuals facing significant disabilities. Disability affects various life dimensions, including access to health services. This study aimed to identify the needs and challenges encountered by people with disabilities and to propose solutions for these issues. MATERIALS AND METHODS: This qualitative content analysis research was conducted at Isfahan University of Medical Sciences in 2019. Participants included faculty members from the rehabilitation school, senior students, therapists, disabled individuals, and their families (23 interviews in total). These participants were chosen for their extensive knowledge of the challenges faced by people with disabilities. Semi-structured interviews were conducted, with informed consent obtained before each interview. The interviews were analyzed using the Graneheim and Lundman content analysis method and MAXQDA software. To ensure data accuracy, the criteria of conformability, credibility, dependability, and transferability were applied. RESULTS: The analysis of the interviews yielded two main categories and 10 subcategories. In the category of disability-related problems, family problems, therapeutic problems, psychological problems, academic problems, and social problems were identified as the most significant. As for solutions, educational solutions, therapeutic solutions, social solutions, research solutions, and solutions for reintegrating patients into normal life were proposed to address the problems faced by disabled individuals. CONCLUSION: People with disabilities are an integral part of any country's society. To adequately address their therapeutic needs, it is essential to equip our health workers with the knowledge and skills tailored to the specific needs and challenges of disabled individuals.